Draft Genome Assemblies of Two Cryptosporidium hominis Isolates from New Zealand - Knox MA; Garcia-R JC; Hayman DTS (American Society for Microbiology, 2021)
Cryptosporidium hominis is a protozoan parasite that causes gastrointestinal disease in humans worldwide. Here, we report on draft whole-genome sequences of two clinical isolates of C. hominis that were purified from patients with cryptosporidiosis in New Zealand.